"I Am, (Therefore and with Difficulty) I Think": An Enactive Reading of Sabina Berman's Autistic Narrator. Issue 1 (1st January 2022) - Lovell, Sue
ABSTRACT: This first novel of Mexican film director, scriptwriter, poet, multi-award-winning playwright, journalist, and political activist, Sabina Berman, appeared in English translation in 2012. Berman's autistic narrator, Karen Nieto, uses notebooks and diaries to produce a memoir-style narrative that undercuts Cartesian understandings of rational human(ist) subjectivity; Nieto is embodied, and embedded in the world, then she attributes meaning. This paper argues that Berman repositions readers in relation to standard human subjectivity and values by consistently calling attention to differences between (an assumed) neurotypical reader and the representation of a neurodivergent narrator. Taking a Disability Rights perspective, Berman refuses to subsume the narrator's neurodivergence to a neurotypical plot by representing her as an autistic savant or allowing her life story to be reduced to pain and suffering through social or medicalized deficits. An enactive reading of this autistic narrative highlights differences between neurotypical and neurodivergent positions without favoring the former as a point of origin or destination thereby facilitating a revaluation of what it means to be human. It highlights embodiment and embeddedness in environment. The paper also examines stylistic features of the text's materiality that engage with echolalia and alexithymia to analyze how they enable defamiliarization to reposition readers.